Primary hyperparathyroidism: recent advances. Issue 4 (July 2018) - Walker, Marcella D.; Bilezikian, John P.
Abstract : Purpose of review: The purpose of this review is to describe recent advances and changes in the evaluation and management of primary hyperparathyroidism (PHPT). Recent findings: Although it has long been recognized that asymptomatic PHPT is associated with bone loss, particularly at cortical skeletal sites when evaluated with dual-energy X-ray absorptiometry, new imaging techniques suggest that trabecular skeletal deterioration as well as clinically silent vertebral fractures and nephrolithiasis are common. Nonclassical targets of asymptomatic PHPT as well as the effect of vitamin D deficiency and treatment upon PHPT presentation have been the subject of recent intense investigation. Randomized clinical trials are now available regarding the effect of parathyroidectomy (PTX) upon both classical and nonclassical target organs. They have confirmed results from observational studies with regard to the skeletal benefits of PTX but have not consistently shown improvements in nonclassical symptoms. Summary: These findings have led to recommendations for more extensive renal and skeletal evaluation and broader criteria for PTX in PHPT. In addition to dual-energy X-ray absorptiometry, vertebral and renal imaging is recommended. When available, trabecular imaging techniques may be helpful. PTX criteria now include subclinical kidney stones, vertebral fractures and hypercalciuria, in addition to those based on age, serum calcium, bone densitometry and renal function.